KEGIATAN REPORTASE BERITA KOTA OLEH WARTAWAN SURAT KABAR HARIAN RAKYAT BENGKULU - Indria - (Professional: Jurnal Komunikasi dan Administrasi Publik, 2014)
The reporters of Rakyat Bengkulu daily newspaper should have the ability and skill to find and collect the facts in accordance with the planned news in reporting activities. In this research, researcher came directly and conducted direct observation into the reporting activities, projection meeting and writing news. Interviews were also conducted with the editors and reporters of Rakyat Bengkulu daily newspapers about the editorial policy. Reporting activities by Rakyat Bengkulu daily newspaper reporters was activities which was started from the meeting projections, seek for information about an issue, mews typing and news editing, followed by the editor decisions whether the news was proper published or not. Keywords: news, reporting activities, reporters